Strength training helps cross-country skiers - Morstoel, K.
Amongst professional cross-country skiing groups, maximum strength training has almost been regarded as taboo. Trainers and physiologists have assumed that strength is of no importance to performances that are dependent upon endurance. A research project at the Department of Sports Science at NTNU is at present disproving this hypothesis. The results after the eight-week training experiment were sensational. One of the groups in the experiment, which consisted of seven professional male cross-country skiers who are all among the very best in the country, improved their endurance by as much as 47 per cent. Half of this progress must be attributed to changes in the training programme, because in comparison the control group was able to show a progress of only 22 per cent. The active skiers in the experimental group performed strength training with very heavy weights and very few repetitive movements three times a week for eight weeks, while the control group followed the ordinary training programme. «The experimental group was able to document enormous progress», says lecturer Jan Hoff, who has carried out this experiment along with Jan Helgerud and cand. philol. Jan Tore Vik. He explains that in theory strength training should have a negative effect on endurance, because the muscle mass increases and the intake of oxygen should become more difficult. But the experiment at the Department of Sports Science demonstrates that this does not necessarily have to be the case. «Strength will increase without enlarging the cross section of the muscles if very heavy weights and few repetitive movements are used. This is because an adjustment of the nervous system takes place. Thus performances are improved without reducing the intake of oxygen to the muscles, says Hoff, who is convinced that these results will create a stir internationally. Endurance was monitored on a so-called poling ergometer that has been developed at the Department of Sports Science, supported by the Department of Optical Measurement Systems and Data Analysis at SINTEF. The ergometer works more or less in the same way as a treadmill would do, on which the professional skier has to use his ski sticks to push himself up a hill which is equivalent to an ascent of four per cent. Heart frequency and intake of oxygen are monitored at the same time as the researcher keeps track of how long the skier can manage to keep up with the treadmill. This is where the experimental group was able to register better endurance than the control group had been able to after weeks of maximum strength training. «I don't know whether my skiing speed has improved after this, but I can feel that I have become stronger», says Oeyvind Skaanes, the professional cross-country skier who, among other achivements, won gold in the men's relay in the World Championship in 1991. He is very interested in a training programme which has equally close monitoring, but he points out that he will stand the real test when he starts skiing this winter. At present this experiment is being repeated with professional female cross-country skiers in order to confirm these results. The plan is to perform a series of combined experiments at a later stage. «So far we have monitored the result of strength training in terms of endurance in the upper part of the body, but we expect to find similar results when we monitor maximum strength training on the leg muscles», says Hoff. But he does not want to comment upon whether the national team will change its training programme because of this. «This is true basic research. We are concentrating on the basic mechanisms, but even so the results of this research are still convincing», says Hoff.